2012
DOI: 10.1002/prca.201100041
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of ischemic and hemorrhagic strokes using a multiplexed, mass spectrometry‐based assay for serum apolipoproteins coupled to multi‐marker ROC algorithm

Abstract: Purpose Typically, apolipoproteins are individually measured in blood by immunoassay. In this report, we describe the development of a multiplexed selected reaction monitoring (SRM) based assay for a panel of apolipoproteins and its application to a clinical cohort of samples derived from acute stroke patients. Experimental Design An SRM assay for a panel of nine apolipoproteins was developed on a triple quadrupole mass spectrometer. Quantitative data for each apolipoprotein were analyzed to determine expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 38 publications
0
32
1
2
Order By: Relevance
“…The application of multiple biomarkers could help elucidate the complex interactions among different organs and systems during and after cardiac arrest10. The combination of markers from different physiological systems can improve risk stratification in diseases such as sudden cardiac death, sepsis, and cerebral vascular insults192021.…”
Section: Discussionmentioning
confidence: 99%
“…The application of multiple biomarkers could help elucidate the complex interactions among different organs and systems during and after cardiac arrest10. The combination of markers from different physiological systems can improve risk stratification in diseases such as sudden cardiac death, sepsis, and cerebral vascular insults192021.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, samples enriched at the protein level are digested after capture and are therefore far less complex. In this case, trypsin digestion is typically fast (2–4 h), more economical and highly reproducible ([13,37,55], this paper). Finally, there is the problem of quantification of non-unique peptides with anti-peptide antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, other proteolytic enzymes such as SV8 (Thermo Fisher Scientific) were used to generate peptides with the desired target sequences. Previous experiments using a concatenated, heavy isotope-labeled synthetic concatenated peptide standard demonstrated consistent tryptic digestion with an average digestion efficiency of 64% [55]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Lopez et al (2012) used a reaction monitoring assay to a panel of nine apolipoproteins. They found that the plasma levels of specific apolipoproteins, including apo C-I and apo C-III, distinguished (with high sensitivity and specificity) IS, HS, and normal patient sample groups from each other [56]. …”
Section: Protein Biomarkers In Ischemic Strokementioning
confidence: 99%